Serum calciotropic hormone levels, and dental fluorisis in children exposed to different concentrations of fluoride and iodine in drinking water - BA, Yue; ZHU, Jiang-yuan; YANG, Yue-jin; YU, Bo; HUANG, Hui; WANG, Gang; REN, Li-jun; CHENG, Xue-min; CUI, Liu-xin; ZHANG, Ya-wei (Chinese medical journal, 2010)
Background High fluoride exposure can result in dental fluorosis.Fluoride and iodine are coexistent in the drinking water of areas in China and may affect the prevalence of dental fluorosis and osteogenesis.The aim of this study was to investigate the relationship between serum calciotropic hormone level.and dentaI fluorisis in children exposed to different concentrations of fluoride and iodine in drinking water.Methods A pilot study was conducted in three villages located in the Kaifeng and Tongxu counties of Henan Province,China in 2006.Children aged 8 to 12 years.born and raised in the three villages were recruited.The fluoride levels in the samples of urine from these children were detected by fluoride ion selective electrode.Calcitonin and osteocalcin levels in the serum,and serum calcium were measured by radioimmunassay and flame atomic absorption spectrometry, respectively.Results Fluoride levels in urine were significantly lower in children from control area（CA）as compared with those from the high fluoride ＆ iodine areas（HFIA）and the high fluoride area（HFA）（P〈0.05 respectively）,and no statistically significant difference was found between the children from HFIA and HFA.Additionally,calcitonin levels in the serum were significantly lower in children from CA and HFA as compared with that from HFIA（P〈0.05 respectively）,and osteocalcin levels in the serum was lower in children from CA than those from HFIA （P〈0.05）.No statistically significant difference in serum osteocalcin concentrations was found between children from HFA and HFIA.Conclusion This study provides an evidence that iodine exposure may modify the serum calciotropic hormone levels related to fluorine exposure.